2016
DOI: 10.2340/00015555-2216
|View full text |Cite
|
Sign up to set email alerts
|

Real-life Data on Patient Characteristics, Cost and Effectiveness of Field-directed Treatment for Actinic Keratoses: An Observational Study

Abstract: Actinic keratoses (AK) occur frequently; however, real-life clinical data on personalized treatment choice and costs are scarce. This multicentre one-year observational study investigated patient-characteristics, cost and effectiveness of methylaminolaevulinate photodynamic therapy (MAL-PDT), imiquimod (IMI) and 5-fluorour-acil (5-FU) in patients with AKs on the face/scalp. A total of 104 patients preferred MAL-PDT, 106 preferred IMI and 110 preferred 5-FU. At baseline, significant differences between treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In a real-life cohort study by van Rijsingen et al, treatments with 5-FU, IMQ and MAL-PDT were compared. 17 They found that treatment with 5-FU 5% had the lowest annual costs (€738), compared with IMQ (€877) and MAL-PDT (€1950), and resulted in the largest reduction of lesions. 17 Our total annual costs for treatment with 5-FU (€433), IMQ (€728) and MAL-PDT (€1621) were lower, which might be explained by the fact that their patients were more severely affected than ours.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In a real-life cohort study by van Rijsingen et al, treatments with 5-FU, IMQ and MAL-PDT were compared. 17 They found that treatment with 5-FU 5% had the lowest annual costs (€738), compared with IMQ (€877) and MAL-PDT (€1950), and resulted in the largest reduction of lesions. 17 Our total annual costs for treatment with 5-FU (€433), IMQ (€728) and MAL-PDT (€1621) were lower, which might be explained by the fact that their patients were more severely affected than ours.…”
Section: Discussionmentioning
confidence: 98%
“…In a real‐life cohort study by van Rijsingen et al ., treatments with 5‐FU, IMQ and MAL‐PDT were compared . They found that treatment with 5‐FU 5% had the lowest annual costs (€738), compared with IMQ (€877) and MAL‐PDT (€1950), and resulted in the largest reduction of lesions .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations